2020
DOI: 10.1080/22221751.2020.1757998
|View full text |Cite
|
Sign up to set email alerts
|

Key mutations in the C-terminus of the HBV surface glycoprotein correlate with lower HBsAg levels in vivo , hinder HBsAg secretion in vitro and reduce HBsAg structural stability in the setting of HBeAg-negative chronic HBV genotype-D infection

Abstract: Increasing evidences suggest that HBsAg-production varies across HBV-genotypes. HBsAg C-terminus plays a crucial role for HBsAg-secretion. Here, we evaluate HBsAg-levels in different HBV-genotypes in HBeAg-negative chronic infection, the correlation of specific mutations in HBsAg C-terminus with HBsAg-levels in-vivo, their impact on HBsAg-secretion in-vitro and on structural stability in-silico. HBsAg-levels were investigated in 323 drug-naïve HBeAg-negative patients chronically infected with HBV genotype-D (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Overall, the different genotypes expressed comparable levels of total HBsAg, except for genotype D1, which synthesized substantial lower levels of the antigen. Similar findings were also described in several in vitro studies ( Sugiyama et al, 2006 ; Sozzi et al, 2016 ; Hassemer et al, 2017 ; Zhang et al, 2017 ), as well as in the serum of patients infected with different HBV genotypes ( Brunetto et al, 2013 ; Riveiro-Barciela et al, 2017 ; Salpini et al, 2020 ). HBsAg expression is regulated by two distinct promoters: Surface promoter I (SPI) regulates the transcription of the 2.4-kb mRNA that encodes the LHBs protein, and surface promoter II (SPII) is responsible for the 2.1-kb mRNA transcription, which directs the translation of MHBs and SHBs.…”
Section: Discussionsupporting
confidence: 88%
“…Overall, the different genotypes expressed comparable levels of total HBsAg, except for genotype D1, which synthesized substantial lower levels of the antigen. Similar findings were also described in several in vitro studies ( Sugiyama et al, 2006 ; Sozzi et al, 2016 ; Hassemer et al, 2017 ; Zhang et al, 2017 ), as well as in the serum of patients infected with different HBV genotypes ( Brunetto et al, 2013 ; Riveiro-Barciela et al, 2017 ; Salpini et al, 2020 ). HBsAg expression is regulated by two distinct promoters: Surface promoter I (SPI) regulates the transcription of the 2.4-kb mRNA that encodes the LHBs protein, and surface promoter II (SPII) is responsible for the 2.1-kb mRNA transcription, which directs the translation of MHBs and SHBs.…”
Section: Discussionsupporting
confidence: 88%
“…These findings could not be extrapolated to our study, since we found that the intrahepatic transcriptome variance was not associated with patient age (not shown), albeit that the HBsAg burden in serum and particularly in the liver was negatively associated with patient age ( Supplementary Figure 2 ). Likewise, infection with HBV genotype D, which was predominant in our cohort and has been shown to be associated with lower serum HBsAg levels [ 23 ], showed no transcriptomic differences compared with samples from patients with non-D genotypes (not shown).…”
Section: Discussionmentioning
confidence: 62%
“…Inactive carriers were selected with a 10-fold difference in serum HBsAg levels (low [≤1000 IU/mL] in 5 and high [≥10 000 IU/mL] in 5) ( Figure 2A ). HBV genotype distribution (not shown) and age (median, 39 vs 36 years in low- and high-HBsAg groups, respectively) and were comparable between groups, albeit older age and genotype D have been associated with lower serum HBsAg levels [ 22 , 23 ]. Surprisingly, we detected only 4 DEGs ( INAVA , SNX32, RBPMS2, and GJA5/CX40 ) between the low- and high-HBsAg groups, with all except GJA5/CX40 increased in the high-HBsAg group ( Figure 2B ).…”
Section: Resultsmentioning
confidence: 99%
“…Of note, Di Lello and colleagues [ 74 ] found a higher prevalence of diagnostic failure mutations in patients infected with HBV/D (33.3%) than those infected with HBV/A (17.4%) or HBV/F (2.3%) ( p < 0.001). Moreover, lower levels of HBsAg secretion for HBV/D compared to other genotypes were observed in several in vitro studies [ 75 , 76 , 77 ], as well as in the serum of infected patients [ 78 , 79 ]. Interestingly, the characteristic 33 nt deletion of HBV/D has been associated with the reduction in HBsAg secretion [ 80 ].…”
Section: Genotype Dmentioning
confidence: 99%